Contusion spinal cord injury upregulates p53 protein expression in rat soleus muscle at multiple timepoints but not key senescence cytokines. Issue 3 (5th February 2020) - Graham, Zachary A.; Goldberger, Abigail; Azulai, Daniella; Conover, Christine F.; Ye, Fan; Bauman, William A.; Cardozo, Christopher P.; Yarrow, Joshua F.
Abstract: To determine whether muscle disuse after a spinal cord injury (SCI) produces elevated markers of cellular senescence and induces markers of the senescence‐associated secretory phenotypes (SASPs) in paralyzed skeletal muscle. Four‐month‐old male Sprague‐Dawley rats received a moderate‐severe (250 kiloDyne) T‐9 contusion SCI or Sham surgery and were monitored over 2 weeks, and 1‐, 2‐, or 3 months. Animals were sacrificed via isoflurane overdose and terminal exsanguination and the soleus was carefully excised and snap frozen. Protein expression of senescence markers p53, p27, and p16 was determined from whole soleus lysates using Western immunoblotting and RT‐qPCR was used to determine the soleus gene expression of IL‐1α, IL‐1β, IL‐6, CXCL1, and TNFα. SCI soleus muscle displayed 2‐ to 3‐fold higher total p53 protein expression at 2 weeks, and at 1 and 2 months when compared with Sham. p27 expression was stable across all groups and timepoints. p16 protein expression was lower at 3 months in SCI versus Sham, but not earlier timepoints. Gene expression was relatively stable between groups at 2 weeks. There were Surgery x Time interaction effects for IL‐6 and TNFα mRNA expression but not for IL‐1α, IL‐1β, or CXCL1. There were no main effects for time or surgery for IL‐1α, IL‐1β, or CXCL1, but targeted t tests showed reductions in IL‐1α and CXCL1 in SCI animals compared to Sham at 3 months and IL‐1β was reduced in SCI animals compared to Sham animals at the 2‐month timepoint. The elevation in p53 does not appear consistent with the induction of SASP because mRNA expression of cytokines associated with senescence was not uniformly upregulated and, in some instances, was downregulated in the early chronic phase of SCI. Abstract : Spinal cord injury leads to sustained protein expression of p53 in paralyzed soleus muscles. This change is not associated with differences in key cytokines associated with cellular senescence.